Aluminum(III) Salen Complexes as Active Photoredox Catalysts. Issue 10 (26th September 2019) - Gualandi, Andrea; Marchini, Marianna; Mengozzi, Luca; Kidanu, Hagos Tesfay; Franc, Antoine; Ceroni, Paola; Cozzi, Pier Giorgio
Abstract : Metallosalen are privileged complexes that have found important applications in catalysis. In addition, their luminescent properties have also been studied and used for sensing and biological applications. Salen metal complexes can be efficient photosensitizers, but they can also participate to electron transfer processes. Indeed, we have found that commercially available [Al(Salen)Cl] is an efficient photoredox catalyst for the synergistic stereoselective reaction of alkyl aldehydes with different bromo ketones and malonates to give the corresponding enantioenriched α‐alkylated derivatives. The reaction was performed in the presence of a MacMillan catalyst. [Al(Salen)Cl] is able to replace ruthenium complexes, showing that also aluminum complexes can be used in promoting photoredox catalytic reactions. Abstract : A benchmark photoredox alkylation of aldehydes is effectively promoted by using 5 mol‐% of the commercially available [Al(Salen)Cl], in the presence of a MacMillan organocatalyst (14 mol‐%) under irradiation with a CFL light bulb.